Insurance Products as Protection for Debtors Due to Failure to Implement Performance in Business Agreements - Nanda Utama (Ekasakti Journal of Law and Justice, 2024)
In business protection, there are instruments that are able to anticipate business losses if one party does not carry out what has been agreed. An instrument called insurance. Insurance products according to Article 246 of the Commercial Code (KUHD) are "an agreement whereby an insurer binds himself to an insured, by receiving a premium, to provide compensation to him for any loss, damage or loss of expected profits, which he may suffer due to an unspecified event”. Insurance itself is useful as protection for the insured in the event of expected losses or profits in the future. As is the case in carrying out a contractual relationship, it cannot be guaranteed that it will run smoothly and according to what has been stated in the agreement. At any time, there is the potential that one of the parties to the agreement will not be able to carry out its obligations and this will result in the creditor not fulfilling their performance. This research is legal research (doctrinal research) with a statutory approach, a conceptual approach and an analytical approach. The results of this research explain that First, In a business agreement, the most important thing is that the parties must carry out the provisions to give something, do something or not do something. Second, Insurance itself is financial security for parties interested in running a business so that the business goal of making a profit can be achieved. Third, In cases where debtors fail to carry out their obligations resulting in defaults covered by insurance, it is an ecosystem of mutually beneficial economic circulation with other economic actors.